DEVELOPMENT OF DATABASE FOR CENTRAL NERVOUS SYSTEM (CNS) DISORDERS AND HERBAL REMEDIES - CHINNA BABU PYDI; SATYANARAYANA RENTALA (International Journal of Pharma and Bio Sciences, 2013)
The Central Nervous System consists of the Brain and Spinal Cord. It contains millions of neurones (nerve cells). The brain plays a central role in the control of body functions, including awareness, movements, sensations, thoughts, speech, and memory. Some reflex movements can occur via spinal cord pathways without the participation of brain structures. The spinal cord is connected to a section of the brain called the brainstem and runs through the spinal canal. Cranial nerves exit the brainstem. The spinal cord carries signals (messages) back and forth between the brain and the peripheral nerves. There are many types of brain and spinal cord tumours & disorders. The importance of the psyche in the cause of disease and in the maintenance of health has been recognized in Ayurveda, the plants often been used to treat the Central Nervous System(CNS) disorders and retain mental ability even at a ripe old age. There is a great need to develop a data base for Central Nervous System physiology, diseases and herbal support to treat CNS disorders. In this project we put an effort to design and develop a web-database to cater the above requirements. The address of the web-database is: https://sites.google.com/site/herbals4cns/